Magnetic Resonance Imaging for Breast Cancer Classification Using Convolutional Neural Networks - Mahiruna, Adiyah; Destriana, Rachmat; Riansyah, Rahmat (Politeknik Negeri Batam, 2025)
Breast cancer remains a leading cause of mortality among women worldwide, emphasizing the urgent need for accurate diagnostic methods. This research addresses the challenges of early detection by leveraging Convolutional Neural Networks (CNNs) for the classification of Magnetic Resonance Imaging (MRI) data. Using a publicly available Kaggle dataset consisting of 54,676 MRI images categorized into